2017
DOI: 10.1249/mss.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Fat Oxidation Rates in an Athletic Population

Abstract: MFO and FATMAX vary significantly between athletes participating in different sports but also in the same sport. Although variance in MFO can be explained to some extent by body composition and fitness status, more than 50% of the variance is not explained by these variables and remains unaccounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
94
4
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 35 publications
9
94
4
9
Order By: Relevance
“…Some studies [5,7,9,17,34,36], but not all [22,27,28], have shown that during endurance exercise women derive proportionally more of the total energy expenditure from fat oxidation with a concomitant lower contribution of carbohydrate (CHO) oxidation compared to men. Furthermore, it has been reported that PFO per kilogram fat-free mass (FFM) and the relative exercise intensity that elicit PFO (Fatmax) are significantly higher in women compared to men [7,26,36]. In line with this, men seem to exhibit a lower metabolic crossover point than women during incremental exercise [36].…”
Section: Introductionmentioning
confidence: 87%
“…Some studies [5,7,9,17,34,36], but not all [22,27,28], have shown that during endurance exercise women derive proportionally more of the total energy expenditure from fat oxidation with a concomitant lower contribution of carbohydrate (CHO) oxidation compared to men. Furthermore, it has been reported that PFO per kilogram fat-free mass (FFM) and the relative exercise intensity that elicit PFO (Fatmax) are significantly higher in women compared to men [7,26,36]. In line with this, men seem to exhibit a lower metabolic crossover point than women during incremental exercise [36].…”
Section: Introductionmentioning
confidence: 87%
“…Skeletal muscle is the primary site for fat oxidation during exercise. Accordingly, MFO was found to correlate ( r = 0.55‐0.66) with the amount of fat‐free mass . More specifically, it appears that a high percentage of slow twitch (ST) muscle fibers ( r = 0.62) are associated with a high MFO .…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, MFO was found to correlate (r = 0.55-0.66) with the amount of fat-free mass. 1,5,7,11 More specifically, it appears that a high percentage of slow twitch (ST) muscle fibers (r = 0.62) are associated with a high MFO. 11 In line, endurance athletes, who have a high oxidative capacity and a high MFO also possess a high amount of ST muscle fibers compared to untrained individuals (60-90 vs 40%-60%).…”
mentioning
confidence: 99%
“…It's important to highlight that the maximal fat oxidation rate during exercise varies largely among athletes. In soccer players, mean maximal fat oxidation rate is at 51.8% VO 2 max, but varies between 22.9% and 88.5% VO 2 max (56) .…”
Section: Fats and Exercisementioning
confidence: 99%